Review of the Nearctic (north of Mexico) species of Elacatis Pascoe (Coleoptera: Salpingidae: Othniinae) - Pollock, Darren A. (Zootaxa, 2018)
The North American (north of Mexico) species of Elacatis were revised, based on external and genitalic structures of adults. Seven species are recognized, though the historical inclusion of E. fasciatus Bland among Nearctic species is very likely based on an erroneous collecting locality. Two new species are described, with type localities (counties only) in parentheses: E. larsoni (Nebraska: Box Butte County) and E. stephani (Arizona: Cochise County). The following new synonym is proposed: Othnius umbrosus LeConte 1861 = Othnius lugubris Horn 1868; therefore, only E. umbrosus (LeConte) is associated with dead/dying conifers in western North America. Larval E. umbrosus are thought to be xylophagous, while adults are very likely predaceous. Elacatis senecionis (Champion) and E. immaculatus (Champion) are recorded from north of Mexico for the first time. A lectotype is designated for Elacatis longicornis Horn. A key to the seven species in Canada and the United States is provided, supplemented with photographic images of habiti and selected structural features. Maps of known distributions, based on geo-referenced locality lists, are provided.